2010
DOI: 10.1186/2047-783x-15-11-475
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical expression of heat shock proteins in the mouse periodontal tissues due to orthodontic mechanical stress*

Abstract: The histopathology of periodontal ligament of the mouse subjected to mechanical stress was studied. Immunohistochemical expressions of HSP27 and pHSP27 were examined. Experimental animals using the maxillary molars of ddY mouse by Waldo method were used in the study. A separator was inserted to induce mechanical stress. After 10 minutes, 20 minutes, 1 hour, 3 hours, 9 hours and 24 hours, the regional tissues were extracted, fixed in 4% paraformaldehyde and 0.05 M phosphate-buffered fixative solution. Paraffin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 29 publications
3
28
0
Order By: Relevance
“…Considering time mechanical stress would be applied, Watanabe et al 12) and Muraoka et al 9,10) were applied where in specimens were subjected to mechanical stresses for 3 hours which caused the movement of the teeth closer to the periodontium. In the control group, specimens were prepared immediately after the release of mechanical stress while in the experimental groups;…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering time mechanical stress would be applied, Watanabe et al 12) and Muraoka et al 9,10) were applied where in specimens were subjected to mechanical stresses for 3 hours which caused the movement of the teeth closer to the periodontium. In the control group, specimens were prepared immediately after the release of mechanical stress while in the experimental groups;…”
Section: Discussionmentioning
confidence: 99%
“…Okazaki et al 8) reported the enhanced expression of HSP47, 60 and 70 after the addition of force on human PDL fibroblasts. Moreover, Muraoka et al 10) observed that mechanical stress in mouse periodontal tissue enhanced the expression of HSP27 and 70 during homeostasis in PDL 9) and suggested that HSP27 acts as a molecular chaperone aside from activating the expressions of Runx2 and Msx2 in osteoblasts on the tension side. HSP has been classified by molecular weight and HSP27 belongs to the family of HSP having low molecular weight.…”
Section: Introductionmentioning
confidence: 99%
“…In orthodontic treatment, remodeling of the periodontal tissue is brought about by mechanical stress due to a correction device and, because of tissue responses to this mechanical stress, the tooth moves [1]. The periodontal tissue responds to different types of stimulus such as mechanical stress and inflammation, to maintain homeostasis, and expresses various proteins to bring about active remodeling of the periodontal tissue [2][3][4][5][6][7][8][9][10][11]. It is important to grasp the kinetics of various factors expressed in the periodontal tissue during orthodontic treatment, as a biochemical basis.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the osteogenesis related factors were also examined using immunohistochemical analysis, such as Runx2, Msx2 5-7) , BMP-2, BMP-4, Smad, p-Smad 8,9) and ALP. Furtheremore, HSPs and p-HSPs [10][11][12][13] were also examined on the orthodontic periodontal tension side.…”
Section: Experimental Groupsmentioning
confidence: 99%
“…Thus, some researchers have examined the immunohistochemical profile change of experimental orthodontic periodontal tissues using animal model. Examined data have been published regarding Runx2 and Msx2 [5][6][7] , BMPs and Smad 8,9) and HSPs [10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%